A purine loop and the primer binding site are critical for the selective encapsidation of mouse mammary tumor virus genomic RNA by Pr77(Gag) - Chameettachal, Akhil (Nucleic Acids Res, 2021)
Retroviral RNA genome (gRNA) harbors cis-acting sequences that facilitate its specific packaging from a pool of other viral and cellular RNAs by binding with high-affinity to the viral Gag protein during virus assembly. However, the molecular intricacies involved during selective gRNA packaging are poorly understood. Binding and footprinting assays on mouse mammary tumor virus (MMTV) gRNA with purified Pr77(Gag) along with in cell gRNA packaging study identified two Pr77(Gag) binding sites constituting critical, non-redundant packaging signals. These included: a purine loop in a bifurcated stem-loop containing the gRNA dimerization initiation site, and the primer binding site (PBS). Despite these sites being present on both unspliced and spliced RNAs, Pr77(Gag) specifically bound to unspliced RNA, since only that could adopt the native bifurcated stem–loop structure containing looped purines. These results map minimum structural elements required to initiate MMTV gRNA packaging, distinguishing features that are conserved amongst divergent retroviruses from those perhaps unique to MMTV. Unlike purine-rich motifs frequently associated with packaging signals, direct involvement of PBS in gRNA packaging has not been documented in retroviruses. These results enhance our understanding of retroviral gRNA packaging/assembly, making it not only a target for novel therapeutic interventions, but also development of safer gene therapy vectors.